Cabozantinib in Combination With Atezolizumab for Advanced Renal Cell Carcinoma: Results From the COSMIC-021 Study. Issue 33 (20th November 2021) - Pal, Sumanta K.; McGregor, Bradley; Suárez, Cristina; Tsao, Che-Kai; Kelly, William; Vaishampayan, Ulka; Pagliaro, Lance; Maughan, Benjamin L.; Loriot, Yohann; Castellano, Daniel; Srinivas, Sandy; McKay, Rana R.; et al.
Abstract : PURPOSE: COSMIC-021 is evaluating cabozantinib plus atezolizumab in patients with solid tumors. We report results from patients with advanced clear cell (cc) and non–clear cell (ncc) renal cell carcinoma (RCC). METHODS: This phase Ib study (NCT03170960 ) enrolled patients age ≥ 18 years with advanced RCC. A dose-escalation stage was followed by expansion cohorts. For cohort expansion, prior systemic therapy was not permitted for ccRCC but allowed for nccRCC. Patients received oral cabozantinib 40 mg once a day (ccRCC and nccRCC) or 60 mg once a day (ccRCC only) plus atezolizumab (1, 200 mg intravenously, once every 3 weeks). The primary end point was investigator-assessed objective response rate (ORR) per RECIST v1.1; the secondary end point was safety. RESULTS: A total of 102 patients were enrolled. Median follow-up was 25.8, 15.3, and 13.3 months for the 40-mg ccRCC, 60-mg ccRCC, and nccRCC groups, respectively. ORR was 53% (80% CI, 41 to 65) in the 40-mg ccRCC group (n = 34) and 58% (80% CI, 46 to 70) in the 60-mg ccRCC group (n = 36), 3% and 11%, respectively, with complete response; median progression-free survival (exploratory end point) was 19.5 and 15.1 months, respectively. In nccRCC (n = 32), ORR was 31% (80% CI, 20 to 44), all partial responses; median progression-free survival was 9.5 months. Grade 3 or 4 treatment-related adverse events (TRAEs) were reported by 71% of patients in the 40-mg ccRCC group, 67% in the 60-mg ccRCC group, and 38% in the nccRCC group; TRAEs leading to discontinuation of both agents occurred in 15%, 6%, and 3% of patients, respectively. There were no grade 5 TRAEs. CONCLUSION: The novel combination of cabozantinib plus atezolizumab demonstrated encouraging clinical activity and acceptable tolerability in patients with advanced ccRCC and nccRCC. Disease control was observed across dose levels and histologic subtypes. Abstract :